EXPERIENCE IN CREATING SORPTION THERMAL TRANSFORMERS - Stepanova, Olesya; Kovalov, Viktor; Shavrin, Yuriy; Danko, Ivan; Chalaev, Murshyd; Posunko, Dmytro (European Science, 2025)
The experience in creating sorption thermal transformers and the prospects for the application of salt adsorbents of the proposed type in thermal energy transformation processes are considered, since by varying the composition and concentration of the act